2020
DOI: 10.1080/15248372.2020.1858835
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Non-symbolic and Symbolic Skills in the Development of Early Numerical Cognition from Preschool to Kindergarten Age

Abstract: The development of (early) numerical cognition builds on children's ability to understand and manipulate quantities and numbers. However, previous research did not find conclusive evidence on the role of symbolic and non-symbolic skills in the development of (early) numerical cognition. The aim of the current study was to clarify the relation between different types of non-symbolic quantity skills, symbolic numerical skills and early numerical cognition. A sample of 43 children was tested at the age of 3.5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Similar results were found in this study. A possible explanation for these results may also be related to the type of test used for the assessment of ANS, as results in favour of training are found in the estimation test (van ‘t Noordende et al, 2021 ), but not in the non-symbolic comparison test. This fact does not call into question the involvement of the ANS in the development of mathematical competence, but these results may be attributable to the measures used.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in this study. A possible explanation for these results may also be related to the type of test used for the assessment of ANS, as results in favour of training are found in the estimation test (van ‘t Noordende et al, 2021 ), but not in the non-symbolic comparison test. This fact does not call into question the involvement of the ANS in the development of mathematical competence, but these results may be attributable to the measures used.…”
Section: Discussionmentioning
confidence: 99%
“…However, early symbolic skills were the greater predictor of later maths achievement. Similarly, van ‘t Noordende et al (2021) reported that symbolic and non‐symbolic skills at age 3½ years were related to children's early maths skills at age 5.…”
Section: Introductionmentioning
confidence: 95%
“…Evidence for the directional relationship between the systems is inconclusive (Goffin & Ansari, 2019), but research supports a positive relationship between non‐symbolic and symbolic abilities, alongside mapping skills, linked to attainment (Toll et al, 2015; van ‘t Noordende et al, 2021; Vasilyeva et al, 2018). However, the mapping abilities of 4½ to 5‐year‐old children in formal schooling remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has shown a stronger association between MA and symbolic number processing than nonsymbolic number processing (e.g., Braham & Libertus, 2018; Colomé, 2019; Dietrich et al, 2015; Starling-Alves et al, 2022). Thus, number format may also impact MA, if symbolic tasks recruit different working memory resources than nonsymbolic tasks (van’t Noordende et al, 2021; Xenidou-Dervou et al, 2015), or if people perceive nonsymbolic tasks to be less “math-like” than symbolic tasks due to their lack of numbers.…”
Section: Math Anxietymentioning
confidence: 99%